Role of Circulating Lymphocytes in Patients with Sepsis. (22nd September 2014) - de Pablo, Raul; Monserrat, Jorge; Prieto, Alfredo; Alvarez-Mon, Melchor
Abstract : Sepsis is a systemic inflammatory response syndrome due to infection. The incidence rate is estimated to be up to 19 million cases worldwide per year and the number of cases is rising. Infection triggers a complex and prolonged host response, in which both the innate and adaptive immune response are involved. The disturbance of immune system cells plays a key role in the induction of abnormal levels of immunoregulatory molecules. Furthermore, the involvement of effector immune system cells also impairs the host response to the infective agents and tissue damage. Recently, postmortem studies of patients who died of sepsis have provided important insights into why septic patients die and showed an extensive depletion of CD4 and CD8 lymphocytes and they found that circulating blood cells showed similar findings. Thus, the knowledge of the characterization of circulating lymphocyte abnormalities is relevant for the understanding of the sepsis pathophysiology. In addition, monitoring the immune response in sepsis, including circulating lymphocyte subsets count, appears to be potential biomarker for predicting the clinical outcome of the patient. This paper analyzes the lymphocyte involvement and dysfunction found in patients with sepsis and new opportunities to prevent sepsis and guide therapeutic intervention have been revealed.